KNOWLEDGE LEVEL OF BROILER BREEDERS IN IRBEL CITY IN BREEDING PROCESS DURING OF THE GROWTH AND INCUBATION PERIODS - Hamed, Ahmed S. (Diyala Agricultural Sciences Journal, 2020)
The study aimed to identifying the level of cognitive of broiler breeders in the breeding process with in of the growth and incubation period, and identifying the relationship between the cognitive level and some independent factors of breeders. The study included 11 agricultural sections in Erbil governorate. And the total breeders broiler (356), were randomly selected in ratio 20% from breeders in all agricultural sections. A number of (71) breeder the data collected by a questionnaire by a personal interview with broiler breeders Which consisted of two parts, the first part attached to factors independent of the educators and the second part attached to measure the level of knowledge for educators. The result showed that these was (77.5%) from breeders with low degrees "between (23.4 - 45.46), and the average was (32.45) degree. The results have proved significant correlation between cognitive level and (age, academic achievement and exposure to extension information's level). As well as the study showed non-significant correlation between cognitive level and (number of year of the work in breeding, number of breeding hall). The study recommended increase of the extension services and activities such as (symposiums, training courses, extension magazines) Thereby increasing the degree of exposure of the information educators extension and thus in order to development cognitive level for breeders